“Los costos de producción de la instalación de líneas en bananeras del taller de funiculares Walter del cantón La Maná, provincia de Cotopaxi. Año 2020” - Gallardo Loor, Adriana Karolina (2021)
The objective of this research was to design a production order cost model that would facilitate the decision-making process at the Walter funiculars workshop in La Maná canton. The problem was related to the lack of a production cost system, the real production costs were unknown, it was also associated with the low level of training of the owner and workers, the deficiencies in the accounting records and the maintenance of a traditionalist management, where a low control over income and expenses prevailed, which seriously complicated the decision-making process. The research was based on information obtained through texts and documented bibliographic references related to cost accounting, production costs and decision making. The methodology applied was mixed, i.e. qualitative and quantitative, which described the processes applied, analyzed and evaluated the problem through research techniques such as interviews and surveys used to collect information. The results obtained showed that there is a high percentage of ignorance of the application of cost methodology by production orders, for this reason the real profits of the production of funicular lines were unknown. It was concluded that the lack of a system can cause losses in the final production, so it is recommended to apply the proposed guide with strategies that help to improve profitability and decision making throughout the production process.